DIMENSIONALITY AND MEASUREMENT INVARIANCE OF A SCHOOL READINESS SCREENER BY ETHNICITY AND HOME LANGUAGE. Issue 7 (28th June 2016) - Quirk, Matthew; Mayworm, Ashley; Edyburn, Kelly; Furlong, Michael J.
Abstract : This study examined the dimensionality and measurement invariance of the Kindergarten Student Entrance Profile (KSEP) when used to rate the school readiness of children from different ethnic backgrounds (Latino or White, non‐Latino), as well as from households where a different language was predominant (Spanish or English). Teachers rated the readiness of 9, 335 children during the first month of kindergarten in four ethnically diverse, medium‐sized school districts in central California. From the total sample, two overlapping subsamples (S1 and S2) were identified. First, a series of confirmatory factor analyses were conducted with S1 ( n = 7, 787) to examine the dimensionality and measurement invariance of the KSEP with children who identified as either Latino or White at the time of kindergarten enrollment. Next, the same set of analyses were replicated with S2 ( n = 9, 234) to examine whether results held for students from households where the primary language spoken was Spanish or English. Results yielded evidence supporting a two‐factor structure encompassing social‐emotional and cognitive dimensions of children's readiness. In addition, results showed the KSEP exhibited measurement invariance across student ethnicities (Latino/White) and home languages (Spanish/English). The results of this study provide psychometric evidence that is particularly important for a universal school readiness screener.